THE MEANING OF THE CONCEPT “TATARS” IN THE MOSCOW KINGDOM DOCUMENTS ON THE TRANS-URALS DURING THE LATE 16th – 18th CENTURIES - Samigulov G.Kh. (Золотоордынское обозрение, 2025)
We habitually perceive the designations “Tatars”, “Bashkirs”, “Voguls”, etc. used in Russian documents of the late 16th – 18th centuries as ethnonyms. Usually, reconstruction of the establishment of certain linguistic/”ethnic” groups is based on the use of these notions in the sources. However, the case with the name “Tatars” is more complicated, as this word often acted as a unifying designation for different groups of communities with similar languages or a similar type of economy. However, this publication focuses on another, somewhat unexpected aspect. The analysis of sources relating to the local population of the Trans-Ural uezds during the late 16th – early 17th centuries showed that, at the early stage of the incorporation of these territories into the Moscow kingdom, the word “Tatars” often did not carry any specific linguistic or cultural load at all. It was used, along with the terms “Voguls” and “Ostyaks”, to denominate any yasak population of the forest and forest-steppe Trans-Ural uezds. Moreover, these three concepts were interchangeable – the same population groups could, in documents, be called Tatars, Voguls, or Ostyaks. At the turn of the 16th and 17th centuries there was a distribution of designations of the yasak and servant population by districts. The autochthonous population of the Tara, Tobolsk, Turinsk and Tyumen uezds began to be unambiguously called “Tatars”. This situation undoubtedly influenced the formation of the Siberian-Tatar identity since the use of the name “Tatars” in relation to the local population for three centuries could not pass without a trace.But there was another aspect; the concept of “Tatars” in the documents concerning the Trans-Urals in the 17th century was also used as a general designation of Turkic-speaking or “steppe” peoples. Tatars could also be referred to as Tartars of the Tumen, Tobolsk, etc. districts, and Bashkirs, natives of the Volga region, Kalmyks, and Kazakhs. Consequently, the name “Tatar” in the sources of the late 16th – 17th centuries appears either as a situational designation for the yasak and servant class of certain uezds, or as a generalised concept that includes groups different in identity (Bashkirs and Kazakhs) or language (Kazakhs and Kalmyks). Thus, it is necessary to rely on the use of the word “Tatars” in this group of sources to reconstruct the history of the current Tatar population in the Trans-Urals and Western Siberia only with great caution.